Batch and dynamic adsorption of Eriochrome Black T from water on magnetic graphene oxide: Experimental and theoretical studies. Issue 1 (February 2018) - Khurana, Ishani; Shaw, Ajay Kumar; Bharti,; Khurana, Jitender M.; Rai, Pramod Kumar
Graphical abstract: Highlights: Magnetic graphene oxide (MGO) is synthesized using salt reduction method. Langmuir monolayer adsorption of EBT is taking place with high adsorption capacity. Removal kinetics of EBT with MGO follows pseudo second order model. Weber-Morris diffusion model indicates strong initial adsorption. Exceptional potential of MGO as a novel commercial filter is depicted. Abstract: In this study we have synthesized a high surface area magnetic graphene oxide (MGO) impregnated with α-Fe2 O3 for the removal of a toxic textile azodye Eriochrome Black T (EBT). MGO was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive analysis of X-rays (EDAX), fourier transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD), Raman, Superconducting quantum interference device (SQUID) and Brunauer-Emmet-Teller (BET) surface area analyzer. Batch adsorption of EBT with MGO was studied using various isotherms and it was found to follow Langmuir monolayer adsorption with 210.53 mg g −1 maximum adsorption capacity. Thermodynamic study indicates the adsorption to be spontaneous and exothermic in nature. The time-dependent adsorption followed pseudosecond order kinetics and intraparticle diffusion model indicates strong initial adsorption and the diffusion is controlled by both boundary layer and intraparticle diffusion. Attempt was made to study the dynamic EBT adsorption, for which a customized filter was prepared. It was observed that MGO has high adsorption capacity in this case as well which led to the conclusion that MGO filters have a great potential to be used commercially, becoming a futuristic adsorbent.